Auswirkungen gesellschaftlicher Krisen auf die digitale und soziale Teilhabe von Adressat: Innen im Sozialraum:Ergebnisse einer Befragung von Fachkräften der Gemeinwesenarbeit in Hessen - Holger Spieckermann; Christiane Nakao; Sonja Preissing; Katrin Sen (IU Internationale Hochschule, 2024)
– Social crises such as the corona crisis and the war in Ukraine do not leave social work untouched. On the one hand, these crises transform society and the social work; on the other hand, they reinforce social and economic inequalities. Since the Covid 19 pandemic, the issue of digitalisation has become more important. Since the first lockdown in 2020, a shift into the digital space can be observed. So, processes of digitalisation poses new questions and challenges for social work - both for the professionals and the clients. In our paper, we will examine and discuss the reflections of social workers on digitalisation in social work practice. For this purpose, we were conducting a survey with professionals of social work on digitalisation in the neighbourhood, e.g. the effects of the pandemic and the Ukraine crisis on social processes in the neighbourhood. Our research questions are: What impact does the pandemic have on the use of digital media in the neighbourhood? How do community work professionals assess the current digital and social changes for their work and their clients? Which competences in the use of digital tools have professionals and inhabitants developed? The pandemic has led to an increased need for digital media and methods in community work. Most professionals have expanded their digital skills during the pandemic in order to overcome the challenges of virtual communication and collaboration. Besides, the Ukraine crisis has increased social inequalities. Migrants, refugees and single parents in particular were hit harder by the consequences of the crisis; e.g. financial worries and discrimination also became more prevalent. In this paper the findings about the knowledge and reflections of the professionals regarding the challenges and opportunities of digitalisation and migration in social work practice will be presented.
Keywords: 300; Pandemie; Digitalisierung; Sozialraum; Ukrainekrieg; Soziale Arbeit mit Adressat:innen